The Effect of Humidity and Temperature on Local Conditions, Especially in Syrdarya, On Increasing the Amount of Wheat Grain Gluten (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
All over the world, breeding trends aimed at improving the quality of agricultural products are becoming increasingly widespread. The leading place in improving the quality of wheat is occupied by the study of new varieties whose grain quality is characterized by resistance to the effects of unfavorable environmental factors. The amount of protein in wheat grain, as well as the mass fraction of gluten, is largely determined by the air temperature during the period of grain formation and ripening.